Star's rescuers: um jogo de tabuleiro colaborativo para o ensino da evolução estelar - Guizzo, Marcos Antonio (2021)
In this dissertation, elaborated in the formative context of the National Professional Master's Graduate Program in Physics Teaching, we present a proposal for the teaching of Stellar Evolution in the discipline of Physics, which was conceived and applied in the 3rd year of High School. As this is the final stage of basic education, students are expected to be familiar with the essential concepts of gravitation and thermology, as well as notions about atomic structure and chemical reactions, which are desirable (but not essential) for the appropriation of new learning. From this perspective, Stellar Evolution will be approached in a transdisciplinary way, relating several concepts of Physics and other Natural Sciences, serving, at this level of education, as an introductory experience in the fields of Astronomy and Astrophysics. This work pays attention to the guidelines of the National Curriculum Guidelines for the New High School (2018) and is in line with the premises of the BNCC High School on the competences and abilities recommended in the Natural Sciences component, which we understand to be discredited by current school programs. Supported by Vygotsky's culturalhistorical theory, complemented by the assumptions of Marshall Rosenberg's model of nonviolent communication, we elaborated the didactic unit and the respective educational product, the board game “Star's Rescuers”. We contemplated the topics related to Stellar Evolution that, in our judgment, proved to be more adequate to the construction of the desired learning. The educational product, adopted as a didactic tool, proved to be of great value for the understanding of Stellar Evolution, as well as for the enrichment of the student's experience concerning to the study of Physics.